2022
DOI: 10.1002/prp2.904
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the role of melatonin in diabetic cardiomyopathy

Abstract: Thirty years ago, the prevalence of diabetic patients was only onefourth the current prevalence. In fact, the current number of diabetic patients has soared to 1 diabetic patient in every 11 people globally. 1 Moreover, diabetes has become the ninth leading cause of death worldwide. According to statistics from the World Health Organization, as of 2000, the number of diabetes patients worldwide had exceeded 170 million, and it is still increasing at an extremely fast rate. It is predicted that the number of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 274 publications
(474 reference statements)
0
3
0
Order By: Relevance
“…Moreover, a major aspect of the melatonin's ability to shelter cardiomyocytes from elevated glucose levels during diabetes likely involves preservation of mitochondrial function [93,94]. The collective findings indicate that melatonin's protection of the heart from deterioration under diabetic cardiomyopathic conditions is unequivocal and multifunctional [95][96][97]. Considering the serious nature of cardiovascular and cardiac damage in individuals suffering with T2D, melatonin supplementation could be considered a reasonable and likely effective means of combating this seriously destructive condition (Figure 5).…”
Section: Melatonin and Diabetic Cardiomyopathymentioning
confidence: 99%
“…Moreover, a major aspect of the melatonin's ability to shelter cardiomyocytes from elevated glucose levels during diabetes likely involves preservation of mitochondrial function [93,94]. The collective findings indicate that melatonin's protection of the heart from deterioration under diabetic cardiomyopathic conditions is unequivocal and multifunctional [95][96][97]. Considering the serious nature of cardiovascular and cardiac damage in individuals suffering with T2D, melatonin supplementation could be considered a reasonable and likely effective means of combating this seriously destructive condition (Figure 5).…”
Section: Melatonin and Diabetic Cardiomyopathymentioning
confidence: 99%
“…Multiple investigations have also shown that SIRT1 activation is neuroprotective in DN in part by enhancing mitochondrial bioenergetics and autophagy [21,22]. Additional studies have also demonstrated that AMPK and SIRT1 help to reduce DN by improving mitochondrial function through the PGC-1α and Nrf2 axis [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Some patients have a hyperglycemia-induced myocardial injury but do not have high blood pressure or coronary artery disease. This disease, termed diabetic cardiomyopathy ( 3 ), is currently of considerable interest among researchers ( 4 ). The underlying mechanisms of hyperglycemia-induced myocardial injury include cardiac inflammation, increased reactive oxygen species (ROS), interstitial fibrosis, and cardiac cell apoptosis ( 2 , 5 ).…”
Section: Introductionmentioning
confidence: 99%